Why IIoT should make businesses rethink security. Issue 7 (July 2019) - Herbert, Sean
Abstract : Companies of all sizes are revolutionising the way modern businesses operate by taking advantage of embedded sensors and cloud computing, making it possible for machines, industrial plants, factories and even construction sites to be connected as part of Industry 4.0. But the practice of securing technology and protecting networks from cybercrime has become increasingly difficult, as demonstrated by the catastrophic threats posed by cyber attacks on nuclear power plants across the US and power grids in the UK energy sector in 2017. Companies of all sizes are revolutionising the way modern businesses operate by taking advantage of embedded sensors and cloud computing. But securing technology and protecting networks has become increasingly difficult. Businesses urgently need holistic solutions that create transparency and traceability at a technical and organisational level. With more-complex IT infrastructures spanning thousands of endpoints, automation has become essential to streamline the detection and patching of vulnerabilities in a timely manner by making sure that every application is fully patched against that specific bug quickly and effectively, argues Sean Herbert of Baramundi.